2021
DOI: 10.3390/ijms22073297
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Rootstock-Mediated Growth and Yield Responses in Salinized Pepper Plants (Capsicum annuum L.) Are Associated with Changes in the Hormonal Balance

Abstract: Salinity provokes an imbalance of vegetative to generative growth, thus impairing crop productivity. Unlike breeding strategies, grafting is a direct and quick alternative to improve salinity tolerance in horticultural crops, through rebalancing plant development. Providing that hormones play a key role in plant growth and development and stress responses, we hypothesized that rootstock-mediated reallocation of vegetative growth and yield under salinity was associated with changes in the hormonal balance. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
1
9
0
9
Order By: Relevance
“…Such effects are highly controlled at the hormonal level, 36 which are in turn known to be altered in response to grafting. 37 Pulp lightness L* was similar in control and grafted plants at the baby and mid-CM stages. However, at late maturity, grafted eggplants maintained a lighter color than the control (Table 1).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Such effects are highly controlled at the hormonal level, 36 which are in turn known to be altered in response to grafting. 37 Pulp lightness L* was similar in control and grafted plants at the baby and mid-CM stages. However, at late maturity, grafted eggplants maintained a lighter color than the control (Table 1).…”
Section: Resultsmentioning
confidence: 84%
“…Given the developmental stages, studies of the observed effects could be caused by the alteration in the polarity of cell expansion. Such effects are highly controlled at the hormonal level, 36 which are in turn known to be altered in response to grafting 37 . Pulp lightness L * was similar in control and grafted plants at the baby and mid‐CM stages.…”
Section: Resultsmentioning
confidence: 99%
“…Our results agree with previous report which suggests that flooding results in lower chlorophyll contents but triploid watermelon has more chlorophyll as compared to diploid watermelon ( Yan et al., 1996 ; Choudhary and Padmanabhan, 2021 ; He et al., 2022 ). Similarly, root fresh weight and shoot fresh weight are important in terms of a plant’s response to stress ( Pires et al., 2015 ; Gálvez et al., 2021 ; Zhang et al., 2021 ). Our results indicated that 3X watermelon possess higher root and shoot fresh weights as compared to 2X watermelon plants ( Garg et al., 2002 ; Kartik et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that grafting vegetable crops onto tolerant rootstocks can improve global plant performance and final productivity under different abiotic stress conditions [6]. To test the role of hormones in this process, Gálvez et al [7] studied rootstock-mediated growth and yield responses in pepper plants, either non-grafted or grafted onto three commercial rootstocks, which were subjected to moderate salinity stress. They showed that developmental and physiological responses of pepper plants were associated with changes in the hormonal balance that helped to improve crop productivity under salinity stress.…”
mentioning
confidence: 99%